Reduction of HIV Persistence Following Transplantation in HIV‐Infected Kidney Transplant Recipients. Issue 5 (3rd April 2014) - Stock, P. G.; Barin, B.; Hatano, H.; Rogers, R. L.; Roland, M. E.; Lee, T.‐H.; Busch, M.; Deeks, S. G.; ,
<x xml:space="preserve">Abstract</x> Chronic inflammation may contribute to human immunodeficiency virus (HIV) persistence through a number of potential pathways. We explored the impact of immunosuppressant therapy on peripheral blood measures of HIV persistence following kidney transplantation. Stored plasma and peripheral blood mononuclear cells prior to transplantation and at weeks 12, 26, 52 and 104 posttransplant were obtained from 91 transplant recipients. In a multivariate model, higher pretransplant plasma HIV RNA level (p < 0.0001) and a longer duration of follow‐up posttransplant (p = 0.09) were associated with higher posttransplant plasma HIV RNA levels. A higher baseline HIV DNA (p < 0.0001) was significantly associated with higher HIV DNA levels posttransplant, while higher CD4+ T cell count (p = 0.001), sirolimus use (p = 0.04) and a longer duration of follow‐up (p = 0.06) were associated with lower posttransplant HIV DNA levels. The association between sirolimus exposure and lower frequency of cells containing HIV DNA levels posttransplant suggest that the immune‐modifying drugs may affect the level of HIV persistence during effect therapy. Future studies of sirolimus as a reservoir‐modifying agent are warranted.